Illite K-Ar and (U-Th)/He low-temperature thermochronology reveal onset timing of Yadong-Gulu rift in southern Tibetan Plateau - Wang, Shiguang; Shen, Xiaoming; Chevalier, Marie-Luce; Replumaz, Anne; Zheng, Yong; Li, Haibing; Pan, Jiawei; Li, Kang; Xu, Xiwei (Frontiers in Earth Science, 2022)
Determining the timing of E-W extension across the NS-trending rifts in southern Tibet is key to test the mechanical models of the latest evolution in the collision between India and Asia. We focus on the southern half of the largest of the seven main rifts, the Yadong-Gulu rift (YGR), which, despite being the focus of numerous studies thanks to its easy access, still lacks direct time constraints. Using illite K-Ar ages of fault gouge from the active Yadong normal fault of the YGR, we directly constrain its onset timing at 9 ± 1 Ma. (U-Th)/He dating of the footwall leucogranite reveals a rapid exhumation of the southern YGR since ∼9 Ma, attesting to its onset activity. Such timing is similar to that estimated for the northern half of the YGR at 8 ± 1 Ma, suggesting that the entire YGR formed at approximately the same time. Our synthesis of published initiation ages of the other main rifts in southern Tibet shows that they mostly fall between ∼23 and 8 Ma, suggesting a clear spatial and temporal pattern of old initiation ages to the west and young to the east. In this case, the formation of rifts in southern Tibet is unlikely caused by slab tearing of the underthruting Indian plate or orogenic collapse. Our study supports that E-W extension in Tibetan Plateau is triggered by a combination of eastward propagation of the Karakorum-Jiali fault zone and divergent thrusting along the curved Himalayan arc.